Lead in Kansas City soils: lead source tracking and assessment of wastewater-derived phosphate for fertilization and lead remediation - Murphy, Jack (My University, 2025)
Lead is a toxic, naturally occurring element in soil that is widely elevated in surface soils due to anthropogenic Pb pollution. Various sources have contributed to soil Pb contamination such as leaded gasoline, lead paint, and industrial activities. Knowing the contributors of Pb to soil is crucial for protecting soils from further contamination, choosing mitigation methods, and public health. Isotope tracing is a source-tracing method that strives to utilize natural isotopic variations for the discernment of different sources of the element. For Pb, this method can identify anthropogenic contributions in soil by observing the similarity in ratios between the soil and the unique isotopic signature sources can have. The first objective of this study is to identify the major sources of Pb contamination in Kansas City, MO. Surface soils (0 to 15 cm) were collected from various residential and vacant sites in the area. Three near-pristine subsurface soil cores from the Konza prairie was also collected as a background. Soils were digested using USEPA method 3051, and concentrations were determined using an inductively coupled plasma- optical emissions spectrometry (ICP-OES). Diluted samples were analyzed for isotope ratios in ICP- Triple quadrupole mass spectrometry (ICP-QQQ). Results showed that Pb isotope ratios of Kansas City sites overlapped with leaded paint and gasoline ratios. Konza Prairie Pb isotope ratios were distinct from Kansas City sites. Phosphorus is a vital nutrient essential for the global agricultural system and maintaining food security for the world’s growing population. As the population continues to grow, so does the demand for these fertilizers for increasing crop yields. Phosphorus fertilizers are derived from phosphate rocks which are a non-renewable resource and will soon be scarce due to their growing demand. Wastewater streams from agricultural and urban areas are a renewable resource that contain high concentrations of nutrients such as P and can be extracted from wastewater in the form of reclaimed nutrient products (RNPs). The objective of the second study is to evaluate the effectiveness of RNP product as an alternative fertilizer and a potential stabilization treatment for Pb in contaminated soils. The RNP for the study was selected based on wet chemical methods and X-ray diffraction (XRD) characterization. The selected RNP had a total P concentration of 12.57% and a citric soluble P content of 35.89% (% of total P). Two P species were identified by XRD; 84.8% octacalcium phosphate (OCP), and 15.2% struvite. Three soils were acquired from a vacant lot different levels of Pb and classified as mild (208 mg/kg), moderate (323 mg/kg), and extreme (2418 mg/kg). Treatments included four P sources, treatments, ammonium polyphosphate (APP), triple superphosphate (TSP), calcium phosphate based RNP, struvite and a control. Phosphorus treatments were applied to soils at equal rates. Completely randomized block design (RCBD) was used with 3 blocks for each plant type (leafy, lettuce and root crop, radish). Lead concentrations were determined with Graphite Furnace Atomic Absorption Spectrophotometry (GFAAS). Other elemental concentrations were determined with ICP-OES, and diluted plant samples Pb isotope ratios were determined with ICP-QQQ. Struvite and RNP treatments showed significant reductions in Pb concentrations for root and leafy crops. Lead concentrations in mild and moderate soils did not exceed FAO/WHO maximum Pb levels for leafy crop. Struvite, RNP and APP showed significant increases compared to the control in P uptake, despite initial excess soil P masking treatment effects. Agronomic levels of P addition had no significant effect on soil Pb bioaccessability. Plant Pb isotope ratios of unamended controls were significantly different than soil Pb isotope ratios, while P treated plants remaining close to the original soil ratios, suggesting selective uptake and/or translocation of soil Pb upon natural attenuation.
Keywords: Lead; Phosphorus; Contamination; Fertilizer